Qualidade da água de barragens subterrâneas do semiárido Potiguar para fins de irrigação - Chianca, Cibele Gouveia Costa (2021)
Underground dams have been widely deployed in the semiarid region of Rio Grande do Norte, a state in Brazilian Northeast, aiming to mitigate the effects caused by water scarcity. Based on this, the goal of this research was to evaluate the water quality from these dams, for irrigation purposes, as well as to analyze the spatial and temporal variability of the electrical conductivity of this resource, through the inverse distance weighting interpolation. The samples were collected in 45 dams, all of them implemented and finalized by the Technical Assistance and Rural Extension Institute from Rio Grande do Norte, at the end of the dry season of 2018 and compared with the samples obtained at the end of the rainy season of 2019. The water quality was determined by the risk assessment of soil salinization and sodification from the United States Salinity Laboratory and by the standards of specific ions toxicity, as the obstruction risk in localized irrigation systems defined by Food and Agriculture Organization of the United Nations. For this purpose, some variables were analyzed: electrical conductivity, hydrogen potential, total suspended solids, total dissolved solids, sodium, potassium, calcium, magnesium, chloride, carbonate, bicarbonate, boron, copper, sulfur, iron, manganese, zinc, chrome, nickel, cadmium and lead. The multivariate techniques of analysis allowed to identify variables that caused higher influence on hydrochemical variation of the water from the dams. The results show that variables related to salinity and to toxicity of ions decreased their rates after the rainy season, while the rates of variables related to obstruction problems at localized irrigation systems increased. Regarding the risk of salinity and soil sodicity, most of the dams were classified as C2-S1. The presence of rural communities without sanitary sewer system, the use of animal waste as fertilizer and the decomposition of organic matter, due to cultivation of grasses around the dams could increase the salinity rates of the water from alluvial aquifers. The alkalinity, the algae presence and the concentration of iron ions are the variables responsible for the obstruction problems at localized irrigation systems. The variables related to salinity present higher influence over the hydrochemical variation of the water from the dams in both studied seasons. The electrical conductivity and chloride ions present the highest load factor of the salinity. Finally, the areas with the highest electrical conductivity at the end of the dry season are similar to the areas obtained at the end of the rainy season